Starting research - Preece, R. A. (Pinter ; Distributed exclusively in the USA and Canada by St. Martin's Press, 1994)
What is research? Elements of scientific method. The logic of scientific method. Information in research. Methods of primary information collection. Organization and analysis of surveys. You can understand statistics. The research question. The research dissertation.